2015
DOI: 10.1371/journal.pone.0144877
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Inhibits Ischemia/Reperfusion-Induced Myocardial Injury in Rats via Downregulation of microRNA-208b-3p

Abstract: BackgroundLuteolin (LUT), a kind of flavonoid which is extracted from a variety of diets, has been reported to convey protective effects of various diseases. Recent researches have suggested that LUT can carry out cardioprotective effects during ischemia/reperfusion (I/R). However, there have no reports on whether LUT can exert protective effects against myocardial I/R injury through the actions of specific microRNAs (miRs). The purpose of this study was to determine which miRs and target genes LUT exerted suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…Luteolin (Lut) is a natural soluble flavone present in many plants. Our previous studies have demonstrated that Lut can protect the myocardium from I/R injury by down-regulating microRNA-208b-3p [17] and the PI3K/Akt pathway [18]. Moreover, decreased expression and activity of SERCA2a can be partly reversed by Lut [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin (Lut) is a natural soluble flavone present in many plants. Our previous studies have demonstrated that Lut can protect the myocardium from I/R injury by down-regulating microRNA-208b-3p [17] and the PI3K/Akt pathway [18]. Moreover, decreased expression and activity of SERCA2a can be partly reversed by Lut [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, cardioprotection is not lost in translation. Then, we reviewed again our previous study which verified the positive cardioprotective effects of Lut against IRI both in Langendorff perfused rat hearts and the H9c2 cells (1). According to the literature (14), the results would be more convincing if the animal model is similar to the clinical setting.…”
mentioning
confidence: 98%
“…The study by Bian et al (1) found that luteolin (Lut) inhibited myocardial ischemia/reperfusion injury (IRI) by decreasing miR-208b-3p and increasing Ets1 expression levels in rats. Cokkinos (2) has written an editorial commentary for this study and considered it to be elegant.…”
mentioning
confidence: 99%
See 2 more Smart Citations